Effects of self‐directed stress management training and home‐based exercise on quality of life in cancer patients receiving chemotherapy: a randomized controlled trial. Issue 6 (20th June 2012) - Jacobsen, Paul B.; Phillips, Kristin M.; Jim, Heather S. L.; Small, Brent J.; Faul, Leigh Anne; Meade, Cathy D.; Thompson, Lora; Williams, Charles C.; Loftus, Loretta S.; Fishman, Mayer; Wilson, Rick W.
Abstract Background Research has shown that self‐directed stress management training improves mental well‐being in patients undergoing chemotherapy. The present study extends this work by evaluating separate and combined effects of stress management training and home‐based exercise. Method Following assessment of mental and physical well‐being, depression, anxiety, exercise, and stress reduction activity before chemotherapy started, patients were randomized to stress management training (SM), exercise (EX), combined stress management and exercise (SMEX), or usual care only (UCO). Outcomes were reassessed 6 and 12 weeks after chemotherapy started. Significance testing of group‐by‐time interactions in 286 patients who completed all assessments was used to evaluate intervention efficacy. Results Interaction effects for mental and physical well‐being scores were not significant. Depression scores yielded a linear interaction comparing UCO and SMEX (p = 0.019), with decreases in SMEX but not UCO. Anxiety scores yielded a quadratic interaction comparing UCO and SMEX (p = 0.049), with trends for changes in SMEX but not UCO. Additional analyses yielded quadratic interactions for exercise activity comparing UCO and SMEX (p = 0.022), with positive changes in SMEX but not UCO, and for stress management activity comparing UCO and SM (p < 0.001) and UCO and SMEX (p = 0.013), with positive changes in SM and SMEX but not UCO. Conclusion Only the combined intervention yielded effects on quality of life outcomes, and these were limited to anxiety and depression. These findings are consistent with evidence that only the combined intervention yielded increases in both exercise and stress management activity. Future research should investigate ways to augment this intervention to enhance its benefits. Copyright © 2012 John Wiley & Sons, Ltd.